Antecedents and Consequences of Outpatient Patient Satisfaction In The Pharmacy Installation of XYZ Hospital - Anggita Petrareni; Margaretha Pink Berlianto (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to identify the factors that influence the satisfaction levels of outpatients in the Pharmacy Department at XYZ Hospital and their impact on patient loyalty. The study involved 208 outpatients. Data was collected through a questionnaire containing 38 questions using a 1-5 Likert Scale based on a judgemental sampling method. The data was analyzed using the SEM method based on PLS. The results indicate that communication and the attitude of pharmacy staff have a positive and significant influence on patient satisfaction. Timeliness in providing services also contributes positively and significantly to patient satisfaction. The availability of medications in a timely and adequate manner, a clean and comfortable pharmacy environment, and prices perceived as reasonable also have a positive and significant impact on patient satisfaction. Furthermore, patient satisfaction positively and significantly affects patient loyalty in the Pharmacy Department at XYZ Hospital, with satisfied patients tending to return for services and recommend them to others.